Alleviating the impact of the geohelminthiases in the COVID-19 crisis - Falah, Pilar Menara; Nurdian, Yudha (International Journal Of Community Medicine And Public Health, 2023)
Alleviating geohelminthiases impact during 2019 coronavirus disease (COVID-19) is complicated. Various efforts have been made to reduce them. Chemoprevention such as annual or biennial mass preventive drugs (MPD) with albendazole or mebendazole as a single dose for at-risk populations, including preschool children, school-age children, adolescent girls, childbearing age women, and pregnant women, is the form of short-term action. Long-term actions are providing clean water, improving sanitation and toilets, banning on the usage of stool as fertilizer, and counseling on a clean and healthy lifestyle (CHL) accompanied by implementing community based total sanitation (CBTS). The challenges of them are inconstancy in observing the programs, chemoprevention coverage growth in at-risk groups, drug resistance manifestation, and weak diagnostic methods.